Efficacy and safety of invasive laser acupuncture (650 and 830 nm) on knee osteoarthritis: A pilot randomized clinical trial - Raeon Jang; Changsop Yang; Jae-Hong Kim; Dongwoo Nam; Jeong-Cheol Shin; Gwang-Cheon Park; Byoung-Kab Kang; Kyung-Min Shin; Ae-Ran Kim (PLoS ONE, 2026)
This pilot study explored the safety and efficacy of invasive laser acupuncture (ILA) using two wavelengths (650 and 830 nm) compared with a sham laser in patients with knee osteoarthritis (KOA). This randomized, parallel-arm, patient- and outcome assessor-blinded, placebo-controlled, single-center clinical trial was designed with three groups (control, 650, and 830 nm), and 45 participants were randomly allocated in a ratio of 1:1:1. All participants were treated with ILA on the more affected side at SP9, SP10, ST34, ST35, EX-LE2, EX-LE4, and GB34 for 10 minutes per session, twice weekly, for a total of 12 sessions over 6 weeks. The primary outcome was the change in pain visual analog scale (VAS) score at rest and during activity at baseline (Visit 1) versus 1 week after intervention completion (Visit 13). Secondary outcomes included VAS scores after six treatments (Visit 7) and 6 weeks after intervention completion (Visit 14), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores, European Quality of Life Five Dimension Five Level Scale (EQ-5D-5L), patient’s global assessment, rescue medication dosage, and responder rate. Changes in the VAS scores at rest (p = 0.0044, Visit 13; p = 0.0001, Visit 14) and during activity (p = 0.0038, Visit 13; p < 0.0001, Visit 14) were significantly different among the three groups. Significant differences were also observed in WOMAC total (p = 0.0278, Visit 7; p = 0.0485, Visit 13; p = 0.0051, Visit 14), pain (p = 0.0073, Visit 7; p = 0.0210, Visit 13; p = 0.0038, Visit 14), function subscale (p = 0.0055, Visit 14), and EQ-5D-5L scores (p = 0.0131, Visit 14). No ILA-related adverse events or significant changes in vital signs or laboratory results were observed during the study. ILA at 650 and 830 nm showed preliminary signals of short-term pain reduction. However, these preliminary findings should be confirmed in larger, rigorously designed clinical trials. Trial registration CRIS registration number: KCT0008860; registered on 10/11/2023 ( https://cris.nih.go.kr/cris/search/detailSearch.do/25506 ).